(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to study the impact of the Barman model in teaching the skills of dribbling and handling in football to students. The researchers applied the experimental approach to a sample of students from the School of Geniuses. The sample consisted of 50 students distributed equally, 20 students as an experimental group and 20 students as a control group. The researchers used the educational method using the steps of the Barman model in learning the skills of dribbling and handling in football. The researchers assumed the existence of significant differences between the results of the pre and post tests of the experimental and control groups, and the existence of significant differences between the results of the post tests of the experimental and control groups in favor of the experimental group. The researchers reached results that indicate the effect of the Barman model in teaching the skills of rolling and handling, and the researchers concluded that the model should be applied in the sports field for activities and other skills.